Post-Anesthesia recovery time in children undergoing hypospadias correction with general anesthesia in bandung - Siagian, Alexander; Rochmah, Elly N; Seciora, Raiza D (ACTA Medical Health Sciences, 2025)
Anesthesia is defined as the loss of pain sensation, with or without the loss of consciousness. After the anesthetic is discontinued and surgery is completed, the patient is routinely managed in the recovery room, also known as the Post Anesthesia Care Unit (PACU). One of the primary goals of PACU is to monitor and document the recovery time before the patient is transferred to a general ward or an intensive care unit. One of the post-operative complications in pediatric patients is delayed emergence from anesthesia. This is defined as the failure to regain consciousness within 30–60 minutes after discontinuation of anesthesia. Delayed emergence is often a residual effect of anesthetic, sedative, and analgesic drugs. Hypospadias is one of the various surgical conditions among pediatric patients. Indonesia reports a relatively high incidence of hypospadias. This study aimed to determine the postoperative anesthesia recovery time following hypospadias correction in children with ASA physical status I and II at Bandung City Hospital from 2017 to 2020. This cross-sectional study utilized secondary data from medical records, with a sample of 69 people meeting the inclusion criteria. The results showed a mean recovery time of 59.70 minutes, with the shortest recovery time being 45 minutes and the longest 135 minutes. Regarding operative duration, 89.9% of cases (62 people) were completed within ≤ 75 minutes, while 10.1% (7 people) required > 75 minutes. DOI : 10.35990/amhs.v4n1.p35-40 REFERENCES Elysabeth ZD. Central nervous system drugs. In: Gunawan S, Setiabudy R, Nafrialdi E, editors. 5th ed. Jakarta: Balai Penerbit FKUI; 2009. p. 122–37. Tanra ARN. Chapter 19: Anesthesia. In: Sjamsuhidayat R, Karnadiharja W, Prasetyono T, Rudiman R, editors. Textbook of surgery. 3rd ed. Jakarta: ECG; 2013. p. 314–30. Neal MJ. At-a-glance medical pharmacology. 5th ed. Jakarta: Erlangga; 2013. p. 52. Latief SA, Suryadi KA, Dachlan MR. Practical guide to anesthesiology. 4th ed. Jakarta: Department of Anesthesiology and Intensive Therapy, Faculty of Medicine, Universitas Indonesia; 2009. p. 29–33, 97, 105, 107–8, 112–3, 117. Sommeng F. Relationship between pre-general anesthesia physical status and recovery time in post-mastectomy patients at RS Ibnu Sina, February–March 2017. UMI Med J. 2019;3(1):47–58. Staroverov D, Ismailova R. Recovery room: Safety island in the operating theatre. Med J Zambia. 2010;36(3):132–5. Krisna DM, AM. Hypospadias: What are its characteristics in Indonesia? Sci Med J Duta Wacana. 2017;2(2):325. Lu W, Tao Y, Wisniewski AB, Frimberger D, Kropp BP. Different outcomes of hypospadias surgery between North America, Europe and China: Is patient age a factor? Nephrourol Mon. 2012;4(4):609–12. Indonesian Urological Association. Pediatric urology in Indonesia. Jakarta: Indonesian Urological Association; 2016. p. 1–74. Dinata DA, Fuadi I, Redjeki IS. Recovery time in pediatric patients undergoing general anesthesia at Dr. Hasan Sadikin Hospital, Bandung. J Anestesi Perioper. 2015;3(2):100–9. Indonesia DKR. Age categories [Internet]. 2009 [cited 2025 Sep 4]. Available from: http://kategori-umur-menurut-depkes.html Fenny AS. Description of recovery time post-general anesthesia with ASA II physical status in minor surgery at RS Dustira, 2017 [Undergraduate thesis]. Cimahi: Universitas Jenderal Achmad Yani; 2017.